DFT Studies on Factors Affecting Non-Linear Optical Properties of N-Salicylidene-Chloroaniline Schiff Bases - M. Soliman, Saied; A. Massoud, Raghdaa; Hagar, Mohamed (Asian Journal of Chemistry, 2015)
The different molecular structure, electronic and spectroscopic aspects affect the non-linear optical properties of N-salicylidene-chloroaniline Schiff bases (1-3) were calculated using DFT/B3LYP method and 6-31G(d,p) basis set. The TD-DFT method has been used to calculate the electronic spectra of these Schiff bases. The longest wavelength p-p* transition band was calculated at 344.0 nm (f = 0.3944) for compound 3. It was found that N-salicylidene-4-chloroaniline (3) has the highest polarizability (a0 = 178.700 a.u.), hyperpolarizability (btot = 820.299 a.u.) and lower energy gap (DE = 4.046 eV). As a result compound 3 is predicted to have the highest non-linear optical activity between the studied compounds. The correlation equation that relate these electronic parameters with their SHG values were predicted.